Status of PD-1 and PD-L1 expression in invasive urothelial carcinoma of the bladder with mismatch repair protein deficiency - Sungu, Nuran; Kıran, Merve M. (Polish Journal of Pathology, 2023)
It has been reported that mismatch repair deficient (d-MMR) tumors show sensitivity to immune checkpoint inhibitors. We aimed to evaluate the correlation of d-MMR and PD-1/PD-L1 expression in invasive urothelial carcinoma of the bladder. Tissue microarray (TMA) tissues were stained PD-1/PD-L1 and MMR proteins. The expression ratio of these markers has been compared with histopathologic parameters. d-MMR tumors were more superficial muscle invasive (p = 0.012). When the d-MMR, and PD-1/PD-L1 expression ratios were examined, a significant correlation was obtained between the d-MMR and PD-L1 expression ratio of > 5% in both the tumor and immune cells (p = 0.02 and p = 0.004, respectively). The expression ratio was higher in the patients without MMR loss. PD-1 and PD-L1expression in those with MSH6 loss was one or none. When PD1/PDL1 expression was compared with histopathological parameters, a significant relationship was observed between tumor grade and depth of muscle invasion. PD-L1 expression was not observed in the superficial muscle invasive tumors. This study was shown the status of d-MMR and PD-1/PD-L1 in invasive urothelial cancers and their correlation with prognostic markers. PD-1/PD-L1 expression may contribute to the progression and poor prognosis of bladder cancer. However, further studies are required to research the clinical utility.